A Study of Suitable Formula for Gluten-free Tart Cups Production - Charoenphun, Narin; Pakeechai, Kanokporn (Journal of Food Technology, Siam University, 2019)
This research aimed to optimize the ingredients to produce gluten-free tart cups. The thirteen formulations of tart cups consisting of mixed flour (non-glutinous rice flour, potato flour and cassava flour), salted butter and icing sugar were studied by using Mixture Design. Physical properties and sensory evaluation by untrained panelists were investigated. Obviously, the mixture response surface contour plots showed that the percentage baking loss of the tart cup varied proportionately with the mixed flour and salted butter content. The specific volume increased with increasing butter content. Moreover, hardness increased with increasing mixed flour content. Interestingly, a suitable formulation of gluten-free tart cup was 50% mixed flour, 30% salted butter and 20% icing sugar, respectively. This formulation had the highest score of appearance, flavor, taste, texture and overall liking. Furthermore, adding riceberry germ, black sesame seed and dried seaweed in tart cups were studied. The results showed that the formula with black sesame seed had the highest average overall liking score (8.13+0.78) with the level of like moderately. In conclusion, gluten-free tart cups are an alternative for consumers who want to avoid gluten containing foods.